Successful Intervention for Pressure Ulcer by Nutrition Support Team: A Case Report - Shigeki Inui; Yuko Konishi; Yoko Yasui; Toshiko Harada; Satoshi Itami (Karger Publishers, 2010)
A 23-year-old woman with heart failure developed pressure ulcer on her sacral area due to a long-term bed rest and impaired hemodynamics. The ulcer improved only slightly after 2 months with povidone-iodine sugar ointment because of severe nausea and anorexia. Then, the nutrition support team (NST) started intervention and estimated the patient's malnutrition from her body weight (30.1 kg), body mass index (BMI) (13.9), triceps skinfold thickness (TSF) (3.5 mm), arm circumference (AC) (17.2 cm) and serum albumin (2.6 g/dl). The NST administrated an enteral nutrition formula through a nasogastric tube and tried to provide meals according to the patient's taste. Although DESIGN score improved to 7 (DESIGN: d2e1s2i1g1n0 = 7) 2 months later, severe nausea prevented the patient from taking any food perorally. However, after nasogastric decannulation, her appetite improved and 1 month later her body weight increased to 32.8 kg, her BMI to 15.2, TSF to 7.5 mm, AC to 19.7 cm and serum albumin to 4.1 g/dl, and the wound completely healed.